Pembagian hadits dari segi kuantitas sanad berupa hadits mutawattir dan hadits ahad - Ain, Failla Aylana (Maliki Interdisciplinary Journal, 2024)
Division The division of hadith in hadith science pays careful attention to the sources of Islamic teachings. In this case, hadith are divided into two main categories based on the number of narrators: mutawatir hadith and ahad hadith. This research examines the division of hadith in Islam into two types based on the quantity of sanad: mutawatir and ahad. The research began with a study of the basic concepts of these two types of hadith through Islamic hadith literature. Primary sources such as Sahih al-Bukhari, Sahih Muslim, and Sunan Abu Dawood are used to analyze each hadith and determine whether it is mutawatir or ahad. Mutawatir hadiths, with a large number of transmitters, are considered a strong and convincing source of Islamic teachings, while ahad hadiths, with a limited number of transmitters, have a lower level of trust. Nevertheless, the Ahad hadith is still recognized as a valid source of Islamic law. In the study used in this article, these two types of hadith have different roles: mutawatir hadith provide a solid foundation for Islamic laws, while ahad hadith often provide additional perspectives. It is important to carry out a critical review of the sanad and matan of hadith to maintain their integrity and authority. Thus, the development of Islamic laws requires a wise balance between these two types of hadith.